Formation and development of psychiatry in Kharkiv: influence of eminent scientists and doctors - Хрол, Наталія Володимирівна; Серікова, Ольга Сергіївна (Psychiatry, Neurology and Medical Psychology, 2019)
The article is devoted to history of formation and development of medical psychiatric care at “Saburova summerhouse” psychiatric hospital as well as  specialists who worked there and later became world-renowned psychiatrists - Vasyl Giliarovsky, Tykhon Ivanovych Yudin, Pavlo Ivanovych Kovalevsky, Mykola Vasyliovych Krainsky, and others. Organization of the Psychoneurological Institute in this territory in 1921 is described in details. With its formation the heyday of psychoneurological scientific life began. In 1961 Department of psychotherapy, psychoprophylaxis and psychohygiene was established as the first such in the world. Development of psychiatry as a science at Kharkiv University during the 19th - early 21st centuries is paid much attention to, as well as the establishment of the Faculty of Medicine as the most important stage in the development of psychiatry within the walls of the oldest Ukrainian Karazin University (1804). There is also a lot of information about P.A. Butkovsky, Professor of Surgery of Mental Illnesses at Kharkiv university, who was the first to create the science of mental illness in Kharkiv. On the basis of his own observations and experiments he compiled the first Russian manual on psychiatry published in 1834 in St. Petersburg, making the author greatly popular. This work became the first independent guide to psychiatry in Russia. The influence and contribution of prominent scientists V.P. Protopopov, M.A. Goldenberg, E.A. Popov, P.V. Voloshyn and other Kharkiv experts to the world and national medical science have been revealed. The role of Anatoliy Ploticher, Professor, Head of the Department of Psychiatry, Ukrainian Psychoneurological Institute, and his development of experimental and psychological research methods in a psychiatric clinic were emphasized in the article. The attention is given to a number of concepts and techniques proposed by Professor A.I. Ploticher, which are taken into account even today and used in the psychiatric scientific and medical institutions of Ukraine. The article compiles and summarizes the contributions of eminent scientists and physicians to the development of psychiatry in Kharkiv.